Cashless Society: Cluster Analysis of Electronic Payment Users in E-Commerce - Shiddiq Sugiono; Reninta Dewi Nugraheni (Universitas Negeri Semarang, 2023)
Due to its ability to allow multiple electronic transactions, e-commerce is one of the ecosystems that helps to create a cashless society. In order to have a general understanding of the development of the cashless society, it is necessary to investigate the characteristics of behavior that underpin cashless transactions in e-commerce in Indonesia. The goal of this study is to examine the characteristics of cashless payment method consumers in Indonesian e-commerce. K-Medoids analysis was used to classify the survey's 519 participants into various groups. The research shows that it is most appropriate to divide users of cashless payments in e-commerce into three groups. Generation Z who are employed are the primary features of the first group. The second is older Millennial Generation cluster characterized by older males in supervisory roles and higher expenses than other groups. The findings also indicate that Generation Z Early Adopters, third cluster, has begun adopting electronic transactions for security purposes. Additionally, each group agreed to adopt electronic transactions for easy of use reasons.